Collateral circulation in pediatric post-thrombotic syndrome. Issue 144 (August 2016) - Avila, M.L.; Feldman, B.M.; Williams, S.; Baena, D.; Montoya, M.I.; Stinson, J.; Kiss, A.; Lara-Corrales, I.; Brandão, L.R.
Highlights: The role of visible collateral circulation in pediatric PTS was explored A simplified scale for assessment of visible collaterals was developed Visible collaterals showed no or only weak correlation with other PTS findings Inter-rater reliability of the simplified scale was almost perfect